Implementasi Nilai Pendidikan Karakter Melalui Upacara Bendera di Sekolah Dasar - Yasin, Nur Ali (Jurnal Humaniora dan Ilmu Pendidikan, 2025)
Purpose: This study aims to describe the implementation of the flag ceremony at SDN 2 Kalipuro and to identify the character education values embedded within this routine activity. The focus is on how ceremonial practices contribute to shaping students’ discipline, responsibility, and national identity. Research Methodology: The study employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation to capture the lived experiences of teachers and students. Data analysis followed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing, ensuring systematic interpretation of findings. Results: The flag ceremony is consistently held every Monday, supported by preparatory staff training on Saturdays. Findings reveal that the ceremony fosters values such as discipline, responsibility, patriotism, religiosity, curiosity, and effective communication. Nevertheless, challenges include the unpaved school yard, student tardiness, incomplete ceremonial attributes, and the absence of a fixed schedule for ceremony instructors, which occasionally disrupt the smooth implementation. Conclusions: The flag ceremony at SDN 2 Kalipuro proves to be an effective tool for instilling character values among students. However, the sustainability and efficiency of this activity require improvements in infrastructure, time management, and organizational consistency. Limitations: The study is limited to one school context and does not measure the long-term behavioral impact of character values on students. Contribution: This research provides insights into the integration of character education through routine school activities. It offers a practical reference for other schools to strengthen character-building initiatives via structured ceremonies.